2- Promoting Epistemic Vigilance Against Racist Attacks on Africans on Mediatised Permanent Education Sites - Mhiripiri, Nhamo Anthony (African Sociological Review, 2021)
This paper analyses how tropes of racism against people of African descent manifest in public texts (permanent education sites) of different genres and forms. The selected permanent education sites include the mediatisation of the public and private lives of the British royal family’s Prince Harry and Meghan’s break away from royal duties, the FIFA World Cup and the English Premier League, the Chinese Museum in Hubei, and other public incidences that provoked racial controversies. These activities, controversies and exhibitions are vehicles through which racism is reproduced as part of the historical global capitalist system. This is the ubiquitous public pedagogy of permanent education. The porous but multifarious dominant sitesdiffuse diverse forms of pedagogical address to put into play a limited range of identities, ideologies, and subject positions that both reinforce neoliberal social relations and undermine the capacity for democratic politics. Critical scholarship has a normative duty to be mindful of all cultural activities and productions, their processes of signification, and implications for humanization and democracy. After conveniently selecting specific mass mediated permanent education sites, this paper theorises and historicises the colonial foundations of racism and the European construction of an imagined racial hierarchy. It then problematises China as an emergent global economic powerhouse located in this gradation, and its contemporary self- identities – both official and public – given notable allegations of incidences of Chinese racism against people of African descent. Popular sites of mediation are not studied for their own sake, but to develop a radical pan-African scholarship strategically positioned to influence public education sites for social transformation and justice. Such vigilant critical decolonial scholarship makes necessary com onse to insidious sites ocultural education.